Cerebral Toxoplasmosis in an Immunocompetent Patient With Confirmed Covid-19 Positive - Fradisha, Monica; Nareswari, Dewi (Syntax Corporation, 2023)
A case of a 30 years-old male patient, diagnosed with cerebral toxoplasmosis, confirmed HIV, with positive COVID-19. Once he came to the emergency department with a chief complaint of left upper and lower limbs weakness progressing for two days. The patient appeared malnourished and was afebrile and assessed to be well hydrated. He was alert but drowsy and had speech difficulty. A focused neurologic examination was performed and revealed a loss of nasolabial fold indicating facial nerve palsy. Neck stiffness was present and there was reduced motoric power in the left upper and lower limb of 2/5, with positive Babinski sign and Chaddock sign. According to brain CT, showed vasogenic cerebral edema and midline shift. Further laboratory exams showed positive IgG antibodies for Toxoplasma, with a titer exceeding 300 IU/ml, positive serum HIV, with CD4 cell count below 200cell/mm3. Complete blood count study highlighted low haemoglobin and elevated white cell count. He tested positive for COVID-19 by nasopharyngeal swab RT-PCR. Chest CT were done and revealed features of viral pneumonia with ground glass opacity appearance. In summary, we present a patient with cerebral involvement of toxoplasmosis possibly facilitated by pre-existing immunodeficiency as an opportunistic infections of HIV, and with COVID-19 complicated as acute infections. This case report reinforces a potential role for other comorbidities, rather than HIV infection as regards SARS-CoV-2 infection outcomes. For better assessment we need to do MRI.